Percepción de la satisfacción del paciente sobre el cuidado de la enfermera en la unidad de hemodiálisis - Pizarro Vásquez, Fiorella Lisset (2019)
This quantitative descriptive research study was conducted at the Hospital "Víctor Lazarte Echegaray" of the District of Trujillo, Department of La Libertad, during the months of April - August 2016, with the purpose of determining what is the perception of the patient satisfaction about the care of the nurse in the Hemodialysis Unit; The sample consisted of 67 patients who attended the Hemodialysis service. The following instruments were used to collect data: Nursing Care Satisfaction Survey according to Patient Perception, prepared by Arteaga (2003), modified by Pizarro (2016) and an Observational Instrument to Monitor Nursing Care, prepared by Meza (1995) and modified by Pizarro (2016). The results found indicate that the patient with the Nursing care that is provided to them meets with a high satisfaction in 83.58%, average satisfaction in a 13.43% and a low satisfaction of 2.99%. The satisfaction of the patients according to dimensions: The courtesy and safety reached the highest percentages of high satisfaction. With average satisfaction we find the responsibility with the highest percentage (59.70%). Finally, the responsibility dimension presented low satisfaction (11.94%); and according to the observational instrument on care given by the nurse, adequate nursing care was found in 80% and inadequate nursing care in 20%.